PENGARUH EDUKASI EVAKUASI MANDIRI TERHADAP KESIAPSIAGAAN MAHASISWA TERHADAP BENCANA GEMPA BUMI - suparmanto, gatot suparmanto; Wulandari, Ika Subekti (Viva Medika, 2021)
Indonesia is one of the countries that has experienced natural disasters due to Indonesia's geographic conditions which are included in the Ring of fire or a series of active volcanoes which often result in volcanic earthquakes and tectonic earthquakes that can cause property and life losses. This condition makes all elements of society obliged to know about preventive measures in disaster conditions, especially earthquake disasters, one of the prevention of the number of casualties during an earthquake disaster is by means of independent evacuation. The community's lack of understanding about the handling of independent evacuation, especially when an earthquake disaster can cause casualties. Students must also have an understanding of self-evacuation in order to improve preparedness and provide knowledge to the wider community. So this research is to determine the effect of independent evacuation training on earthquake disaster preparedness by using a research sample of 110 students conducted in august 2020 by following health protocol because it is still a covid pandemic 19. This type of research is a quasi experimental design with one group pre and posttest with data analysis methods using Wilcoxon showing the p value = 0.000 (p value <0.05) with the results of the research showing that before training was not ready 75%, less ready 35%, ready 0%, and after training the category of not ready is 0%, 14 people are not ready or 13%, and those who are ready are 96 respondents or 86%. So showing independent evacuation training can improve student preparedness against earthquakes.